The cost benefit of algal technology for combined CO2 mitigation and nutrient abatement - Judd, Simon J.; Al Momani, F. A. O.; Znad, Hussein; Al Ketife, Ahmed M. D. (Elsevier, 2016)
The use of microalgae culture technology (MCT) for mitigating CO2 emissions from flue gases and nutrient discharges from wastewater whilst generating a biofuel product is considered with reference to the cost benefit offered. The review examines the most recent MCT literature (post 2010) focused on the algal biomass or biofuel production cost. The analysis reveals that, according to published studies, biofuel cost follows an approximate inverse relationship with algal or lipid productivity with a minimum production cost of $1 L−1 attained under representative conditions. A 35–86% cost reduction is reported across all studies from the combined harnessing of CO2 and nutrients from waste sources. This compares with 12–27% for obviating fertiliser procurement through using a wastewater nutrient source (or else recycling the liquor from the extracted algal biomass waste), and 19–39% for CO2 fixation from a flue gas feed. Notwithstanding the above, economic competitiveness with mineral fuels appears to be attainable only under circumstances which also feature: a) The inclusion of cost and environmental benefits from wastewater treatment (such as the energy and/or greenhouse gas emissions benefit from nutrient and CO2 discharge abatement), and/or a) Multiple installations over an extended geographic region where flue gas and wastewater sources are co-located.
Keywords: Algae; Cost; Flue gas; Wastewater